Designing Impactful STEAM Project-Based Learning for Brebes Science Teachers through Local Context Integration - Muriani Nur Hayati Hayati; Purwo Susongko; Lufia Krismiyanti; Novi Ratna Dewi; Bayu Widiyanto; Fahmi Fatkhomi; Muhamad Taufiq; Eric Nketia Gyebi (Jurnal Pemberdayaan Masyarakat, 2026)
In the 21st century, creativity, critical thinking, and problem-solving have become essential, especially in the education sector. However, the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach is effective in improving these skills. Many science teachers struggle to translate conceptual understanding into authentic classroom practice. The objective of this community service is to assess the competence of 30 science teachers from Brebes Regency in planning impactful STEAM-based learning. The methods used were SMART objectives with the DACUM technique. The implementation stages were carried out through five community service programs, namely socialization, training, technology transfer, mentoring, and program sustainability. The results of the study showed a very high level of understanding (93.60%) of the STEAM concept and their ability to design lesson plans. In addition, more than 50% of the participants successfully designed draft lesson plans for STEAM projects relevant to the local context of Brebes and presented them at a results seminar. This community service evaluation focused on short-term pedagogical outcomes rather than long-term impact. Therefore, this community service program aims to provide a foundation for advanced STEAM professional development, focusing on design thinking, authentic integration of local problems, and sustainable classroom implementation.